2021
DOI: 10.3390/biomimetics6040068
|View full text |Cite
|
Sign up to set email alerts
|

Tilted Arch; Implementation of Additive Manufacturing and Bio-Welding of Mycelium-Based Composites

Abstract: Bio-based materials have found their way to the design and fabrication in the architectural context in recent years. Fungi-based materials, especially mycelium-based composites, are a group of these materials of growing interest among scholars due to their light weight, compostable and regenerative features. However, after about a decade of introducing this material to the architectural community, the proper ways of design and fabrication with this material are still under investigation. In this paper, we trie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Depending on the application, growth can continue within formworks [ 38 , 39 ]. Some studies explored the extrusion of the substrate mixtures through additive manufacturing [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Some of the parameters that affect the resulting material properties in this phase are the duration of growth, environmental conditions such as temperature and relative humidity, and CO 2 concentration [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the application, growth can continue within formworks [ 38 , 39 ]. Some studies explored the extrusion of the substrate mixtures through additive manufacturing [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Some of the parameters that affect the resulting material properties in this phase are the duration of growth, environmental conditions such as temperature and relative humidity, and CO 2 concentration [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, developing nations present a huge opportunity in terms of the agricultural, wood waste being and municipal waste, that can be used for the fabrication of fungal biocomposites. In addition to the usage of raw materials from agricultural cellulose-based materials, studies have also reported the usage of waste materials like egg cartons, cardboard, newspaper, and paper cups [63]. Lately in India, there is a significant increase in the cultivation of hemp which has relatively less water requirement.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a living composite made with Ganoderma resinaceum responds to pressure by changing its electrical activity [ 17 ]. Moreover, mycelium can be maintained active to enable production of large size mycelium composites, for instance to make mycelium connections between mycelium panels [ 15 , 18 , 19 ].…”
Section: Fungal Materialsmentioning
confidence: 99%